(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
Critical review on polyurethane hybrid nano composite paper gives knowledge on its techniques and their applications. In addition to the scientific framework for the advancement in the polymer matrix hybrid nano composite research, the critical review provides an ample discussion on technology, characterization, processing and its applications on polyurethane hybrid nano composites.